GENDER DIFFERENCES IN SUCCESSFUL AGING: LONGITUDINAL MEMORY RESILIENCE IN AN AUSTRALIAN COHORT. (16th November 2018) - Maccora, J; Peters, R; Anstey, K
Abstract: Among many proposed models of Successful Aging, SuperAgers have been defined as memory-resilient older adults, who perform as well as, or better than, adults many years younger on tests of memory recall. Most research on SuperAgers to date has involved cross-sectional examinations or small volunteer-recruited samples, with limited scope to consider gender differences over time. The aim of this study was to use a large randomly-recruited community sample to investigate whether gender differences play a role in later-life memory resilience and to examine whether longitudinal slopes in memory recall scores differ by gender. SuperAgers were identified in the Path Through Life (PATH) cohort study (eligible population: n=1663; 49.5% female; mean age 70.6 ± 1.5). A SuperAger was defined as a participant recruited age 60–65 who, for three consecutive waves of data collection, scored as well as, or better than, the median for participants of the same gender recruited age 20–25 on tests of immediate and delayed recall using the California Verbal Learning Test. Random effects regression models were used to measure and visualize differences in longitudinal slopes in CVLT test scores between female and male SuperAgers and the rest of the population. Our analysis found that, despite using gender-appropriate cut-offs to identify SuperAgers, there was a higher prevalence among women (8.6%) than men (5.3%). Longitudinal slopes showed a lack of expected decline in memory recall scores over time for SuperAgers compared to non-SuperAgers, however gender stratification revealed that this positive slope applied only for female SuperAgers and not for males.